2022
DOI: 10.3390/su14148844
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Level of Use of the Industry 4.0 Solutions in the COVID-19 Pandemic Era: Results of Empirical Research

Abstract: Changes in the world’s situation and the need to be competitive and less dependent on the global economy lead to improvements in many organisations. Together with business model transformation, using the latest technologies such as augmented reality, autonomous robots, mobile technologies, big data, cloud computing, and others known as an Industry 4.0 pillars, enterprises are changing the industry status quo. These technologies are widely described and studied in the literature, mainly on the example of large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Main results from this study are quite in accordance with that coming from other studies performing statistical analysis on the penetration level of I4.0 technologies. As reference example, the study of Michna and Kruszewska 97 performed statistical analysis on a panel of about 125 worldwide industrial participants, highlighting that AM is much more often used, together with AR, simulation, big data & analytics, integration of horizontal and vertical systems and cloud computing. Detailed results of the statistical analysis, in terms of mean, median, mode, and standard deviation can be found in the paper.…”
Section: Industrial Applications Descriptionmentioning
confidence: 99%
“…Main results from this study are quite in accordance with that coming from other studies performing statistical analysis on the penetration level of I4.0 technologies. As reference example, the study of Michna and Kruszewska 97 performed statistical analysis on a panel of about 125 worldwide industrial participants, highlighting that AM is much more often used, together with AR, simulation, big data & analytics, integration of horizontal and vertical systems and cloud computing. Detailed results of the statistical analysis, in terms of mean, median, mode, and standard deviation can be found in the paper.…”
Section: Industrial Applications Descriptionmentioning
confidence: 99%
“…Mexico has been integrating Industry 4.0 into organizations with advanced technologies for production processes, robotics, digitalization, data management, analytics, and more. A study found that the level of use of I4.0 solutions in Mexico was high at 86.4% [9]. However, most of the South American countries show low I4.0 technological development as it is an exporting country [10,11].…”
Section: Introductionmentioning
confidence: 99%